Development of mathematical model of thermoanemometric flowmeter for measuring the flow of biofuel - Безвесильная, Елена Николаевна; Ильченко, Андрей Владимирович; Ткачук, Андрей Геннадьевич (Technology audit and production reserves, 2014)
The paper deals with today’s existing instruments for measuring the flow of fluid and fuel, their classification is given. The structure and operating principle of a thermoanemometric flowmeter for measuring the biofuel flow was analyzed. A mathematical model of a temperature field in the biofuel flow was developed. It allows accurately determine the flow. The corresponding modeling was carried out. It was found that the volume fuel flow depends on the thermocouple temperature measurement errors in the range of relative errors from 0.01 to 1.0%. For improving the performance of the thermoanemometric flowmeter, a special neuroprocessor that will compensate for random and dynamic measurement errors using artificial neural networks should be included to the computer architecture. The error of measuring the fuel flow will be less than 1% when the measurement error of the heater temperature is 1%. The results can be applied in the design of new highly precise thermoanemometric flowmeters for measuring the biofuel flow.